Anticancer, Enhanced Antibacterial, and Free Radical Scavenging Potential of Fucoidan- (Fucus vesiculosus Source) Mediated Silver Nanoparticles. (30th September 2021) - Rajeshkumar, S.; Aboelfetoh, Eman F.; Balusamy, Sri Renukadevi; Ali, Daoud; Almarzoug, Mohammed H. A.; Tesfaye, Jule Leta; Krishnaraj, Ramaswamy
Abstract : The present research displays the green synthesis of stable silver nanoparticles (AgNPs). The aqueous solution of Fucoidan from Fucus vesiculosus source (brown marine algae) is used as a reducing and capping agent. UV-Vis spectroscopy, XRD, FT-IR, SEM, EDX, and TEM with selected area electron diffraction are used to characterize the synthesized silver nanoparticles (AgNPs). The synthesized AgNPs exhibit a surface plasmon resonance at 430 nm after 24 h. The characterization results showed that AgNPs are crystalline in nature and exhibit mostly spherical shapes with an average diameter of 4-45 nm. Silver nanoparticles showed effective antibacterial activity against representative pathogens of bacteria. The activities of commercial antibiotics were enhanced by impregnation with the synthesized AgNPs. It also shows good fungicidal and anticancer activity against liver and lung cell lines and shows significant antioxidant efficacy (84%) at 10 μ g/ml AgNP concentration against DPPH. The utilization of environmentally synthesized AgNPs offers numerous benefits of ecofriendliness and compatibility for biomedical applications.